Experiments in square lattice design with some common treatments added to each block analysis with recovery of inter-block information. - Oliveira, Antônio Carlos de (Pesquisa Agropecuaria Brasileira, 2014)
Intrablock analysis and analysis with recovery of interblock information are considered for the case in which experirnents are designed in square lattices, but some common treatments are added to each block. Formulas for sums of squares in the analysis of variance, the adjusted treatment means and the variances of treatment differences were obtained. An example is given for illustration